Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1159/000126067
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Inflammatory Effects of Hepatocyte Growth Factor

Abstract: Hepatocyte growth factor (HGF) is known to influence a number of cell types and regulate various biological activities including cytokine production, cell migration, proliferation and survival. Thus, HGF is now recognized to be a key factor in the prevention and attenuation of disease progression. We have reported that HGF reduces allergic airway inflammation, airway hyperresponsiveness, remodeling and development of Th2 cytokines as well as growth factors such as transforming growth factor-β in vivo. In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Another study indicated that treatment with HGF potently suppressed dendritic cell functions such as antigen-presenting capacity, both in vitro and in vivo , thus downregulating antigen-induced Th1 and Th2 immune responses in a mouse model of allergic airway inflammation ( 50 ). HGF has been suggested to suppress airway hyper-responsiveness, inflammation, remodeling, and eosinophil function in asthma ( 51 ). Okunishi et al ( 52 ) reported that HGF suppresses antigen-induced T-cell priming by regulating the functions of dendritic cells through IL-10 downregulation in the antigen-sensitization phase.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that treatment with HGF potently suppressed dendritic cell functions such as antigen-presenting capacity, both in vitro and in vivo , thus downregulating antigen-induced Th1 and Th2 immune responses in a mouse model of allergic airway inflammation ( 50 ). HGF has been suggested to suppress airway hyper-responsiveness, inflammation, remodeling, and eosinophil function in asthma ( 51 ). Okunishi et al ( 52 ) reported that HGF suppresses antigen-induced T-cell priming by regulating the functions of dendritic cells through IL-10 downregulation in the antigen-sensitization phase.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulated expression of extracellular proteases is crucial for pro-cancerous pathways as this enables efficient remodeling of the extracellular matrix as well as cleavage and activation of growth factors and their receptors. Interestingly, a truncated and secreted SPINT2 may act as an inhibitor for the activator of hepatocyte growth factor (HGF) and HGF is prominently expressed in lung tissue and is linked to reduced expression of Th2 cytokines and TGFβ, reduction of allergic airway inflammation, airway hyperresponsiveness and remodeling as well as reduced recruitment of eosinophils to the site of allergic inflammation in vivo [110,111]. This suggests that SPINT2 might enhance Th2 response in allergic airway inflammation by inhibiting HGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support this latter hypothesis is shown by the enhanced inflammatory responses induced following endotoxin exposure to IL-6 −/− mice[9], although, the authors never suggest a biochemical mechanism to explain why this unanticipated phenomenon occurs. HGF, a cytokine widely known for perpetuating liver regeneration, has also been described as having anti-inflammatory properties in cases of persistent inflammation[27], [28], [29], [31], [32], [33]. Importantly, the expression of HGF is induced by IL-6 while its regulation is controlled via acute phase proteins (urokinase and PAI-1) that are also induced following IL-6 stimulation.…”
Section: Discussionmentioning
confidence: 99%